Extracorporeal membrane oxygenation complications are not causal for mortality in patients with infarct-related cardiogenic shock: a mediation analysis of the extracorporeal life support in infarct-related cardiogenic shock (ECLS-SHOCK) trial : clinical investigation - Thevathasan, Tharusan; Alyahoud, Mohamad; Freund, Anne; Akın, Ibrahim; Fichtlscherer, Stephan; Zeymer, Uwe; Feistritzer, Hans-Josef; Pöss, Janine; Jobs, Alexander; Roßberg, Michelle; Jung, Christian; Skurk, Carsten; et al. (Critical care medicine, 2025)
Objective:  - Recently published randomized controlled trials and an individual patient data meta-analysis showed that the routine use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) did not reduce mortality compared with medical therapy alone in patients with acute myocardial infarction complicated by cardiogenic shock (AMI-CS). The objective of this study was to investigate whether possible VA-ECMO-related medical complications are associated with increased mortality risk, which might explain the observed equipoise among mortality outcomes between VA-ECMO and usual care. - Design:  - Sub-analysis of the randomized Extracorporeal Life Support in Infarct-Related Cardiogenic Shock (ECLS-SHOCK) trial. - Setting:  - Multicenter, international randomized controlled trial across 44 centers specialized in treating AMI-CS. - Patients:  - Adults patients with AMI-CS. - Interventions:  - Patients received either routine VA-ECMO support or medical therapy. - Measurements and Main Results:  - The rate of complications and mortality as well as causes of death within 30 days. In total, 417 patients were included in this analysis. Moderate and severe bleeding as well as peripheral vascular complications requiring intervention were classified as possible VA-ECMO-related complications. A total of 88 patients (21.1%) developed possible VA-ECMO-related complications, which mostly occurred within five days after randomization and more frequently in the VA-ECMO group than in the control group: 49 (23.4%) vs. 20 (9.6%) patients, p < 0.001 for bleeding and 23 (11.0%) vs. 8 (3.8%) patients, p equals to 0.008 for peripheral vascular complications, respectively. Only four patients died from bleeding as the primary cause of death. Causal mediation analyses revealed no significant mediation effect of possible VA-ECMO-related complications on 30-day mortality. Logistic regression analyses of possible VA-ECMO-related complications confirmed no significant associations between the frequency of VA-ECMO-related complications and mortality. - Conclusions:  - VA-ECMO use in patients with AMI-CS was associated with increased frequencies of moderate to severe bleeding as well as vascular complications warranting intervention. However, these possible VA-ECMO-related complications did not mediate an increased mortality risk. - Trial Registration:  - ClinicalTrials.gov, protocol: NCT03637205; August 2018.
Gesehen am 20.01.2026